An introduction to sociology - Browne, Ken, 1951- (Blackwell ; Polity Press, 1998)
Introducing sociology. Social stratification. Social class in modern Britain. Wealth, income, and poverty. Gender role socialization. Women. Ethnicity and race. Power and politics. The mass media. Social control, deviance, and crime. The family and marriage. Schooling in Britain. Inequality in education. Religion. Work and leisure. Population. Health and illness. Doing sociological research.